2009
DOI: 10.1002/cne.22209
|View full text |Cite
|
Sign up to set email alerts
|

Depression of Ca2+/calmodulin‐dependent protein kinase II in dorsal root ganglion neurons after spinal nerve ligation

Abstract: The enzyme calcium/calmodulin-dependent protein kinase II (CaMKII) is associated with memory and its α isoform is critical for development of activity-induced synaptic changes. Therefore, we hypothesized that CaMKII is involved in altered function of dorsal root ganglion (DRG) neurons after neuronal injury. To test this hypothesis, Sprague–Dawley rats were made hyperalgesic by L5 and L6 spinal nerve ligation (SNL), and changes in total phosphorylated and unphosphorylated CaMKII (tCaMKII) and phosphorylated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 49 publications
(68 reference statements)
3
18
0
Order By: Relevance
“…This is consistent with our previous histological observations showing pCaMKII in DRG sensory neurons using a phospho-specific Thr286/287 antibody (Kojundzic et al, 2010). To additionally confirm autonomous CaMKII in resting neurons, we tested CaMKII activity in DRG lysates using the specific peptide substrate AC2.…”
Section: Resultssupporting
confidence: 93%
“…This is consistent with our previous histological observations showing pCaMKII in DRG sensory neurons using a phospho-specific Thr286/287 antibody (Kojundzic et al, 2010). To additionally confirm autonomous CaMKII in resting neurons, we tested CaMKII activity in DRG lysates using the specific peptide substrate AC2.…”
Section: Resultssupporting
confidence: 93%
“…Further developmental and subcellular distributions of these two isoforms are seen in the brain (Ouimet et al, 1984, Erondu and Kennedy, 1985, McGuinness et al, 1985, Burgin et al, 1990, Ochiishi et al, 1998) and spinal cord (Terashima et al, 1994), which is compatible with the view that different CaMKII isoforms have particular tissue-specific activities. Although β, γ, and δ isoforms can also be expressed in many tissues, including neurons and support cells in the brain (Ouimet et al, 1984, Tobimatsu and Fujisawa, 1989, Sakagami and Kondo, 1993), prior reports of CaMKII expression in DRGs have shown immunohistochemical colocalization with neuronal markers (Bruggemann et al, 2000, Carlton, 2002, Carlton and Hargett, 2002, Kojundzic et al, 2010), and our present observations indicate that all four (α,β,γ,δ) CaMKII isoforms are expressed in DRGs.…”
Section: Discussionsupporting
confidence: 51%
“…expression or regulation) is diminished with axotomy. In support of this hypothesis, our immunohistochemical characterization indicated a decrease of autophosphorylated CaMKII (pCaMKII) in sensory neuron somata after SNL (Kojundzic et al, 2010). In the present study we examine the influence of injury upon expression of specific CaMKII isoforms using the SNL model, which has two populations of injured neurons.…”
Section: Introductionsupporting
confidence: 64%
“…Previous reports demonstrated that CaMKIIα in adult animals is expressed in ∼40% of DRG neurons coexpressing markers for peptidergic and non-peptidergic nociceptors, including TRPV1 (Brüggemann et al, 2000;Carlton and Hargett, 2002;Ichikawa et al, 2004;Isensee et al, 2014b;Kojundzic et al, 2010;Pattinson et al, 2006). CaMKII directly Representative HCS microscopy images of cultured UCHL1-positive sensory neurons isolated from adult rats at 6 weeks of age (W6 group) and labeled with antibodies specific for the classical nociceptive markers TRPV1 and Na v 1.8, the two kinase isoforms PKA-RIIβ (RIIβ) and CaMKIIα, and NF200 as a marker for the mostly non-nociceptive myelinated mechanoreceptive neurons and proprioceptors.…”
Section: Camkiiα Expression Develops Postnatally and Is Maintained Thmentioning
confidence: 99%